A hydroxyapatite sub-nanowire aerogel and its preparation method and application
By preparing hydroxyapatite sub-nanowire aerogel, the problems of insufficient morphology, hydrophobicity and thermal insulation of nanowire aerogels in the prior art are solved, and aerogel materials with high stability, high temperature resistance, hydrophobicity and low thermal conductivity are achieved, with a wide range of thermal insulation and thermal insulation application prospects.
Patent Information
- Application Number
- CN202410596781.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-14
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-05-14
AI Technical Summary
In the prior art, the micromorphology, hydrophobicity and thermal insulation of hydroxyapatite nanowire aerogels still need to be improved, and they have not effectively combined with the advantages of aerogels and nanowires.
By mixing the surfactant and ethanol, adding aqueous solutions of calcium, strong alkali and phosphorus sources, and carrying out reactions under sealed conditions, hydroxyapatite sub-nanowires were obtained, which were then dispersed and lyophilized to prepare a hydroxyapatite sub-nanowire aerogel with stable structure, high temperature resistance, high hydrophobicity and low thermal conductivity.
It has achieved improvements in structural stability and high temperature resistance of aerogels, and has high hydrophobicity and low thermal conductivity, which is suitable for the fields of insulation and insulation.
Smart Images

Figure CN118495486B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel preparation, and in particular to a hydroxyapatite sub-nanowire aerogel and a preparation method and application thereof. Background Art
[0002] Aerogel is a mesoporous material with a nanoscale structure. It is a solid material with disordered mesoporous shapes, irregular but interconnected, and a high specific surface area (>800m 2 / g), low density (<100kg / m 3 ) and porosity of more than 80%. Due to the nanoscale pore size of aerogel, its thermal conductivity at room temperature and pressure is lower than that of air in free space, so aerogel is also called super thermal insulation material. Due to these excellent properties, aerogel materials are widely used in aerospace, energy, chemical industry, construction and other fields.
[0003] Compared with nanoparticles, one-dimensional nanomaterials have a higher aspect ratio and have important application prospects in the development of nanodevices; nanoscale materials aggregate to form large-sized bulk aerogel materials, which are more valuable for practical applications. Among the many nanostructured materials, one-dimensional hydroxyapatite nanomaterials with a high aspect ratio are one of the hot research topics at present. At present, there are methods for preparing aerogels from nanomaterials. For example, patent CN115572407A discloses a method for preparing heat-insulating aerogels using aramid nanofibers as base materials, composite nanocellulose and hydroxyapatite nanowires. The overall thermal conductivity of the obtained composite aerogel is 31.09mW / m·k, but the hydroxyapatite nanowires of the invention are only used as auxiliary materials to enhance the stability of the aerogel; patent CN107892286A discloses a hydroxyapatite ultra-long nanowire slurry aerogel, which uses hydroxyapatite ultra-long nanowires as raw materials to prepare hydroxyapatite ultra-long nanowire aerogels. The hydroxyapatite nanowires have a diameter of 10 to 100 nanometers and a length of 20 to 2000 microns. The water contact angle of the aerogel is 144.7°, and the room temperature thermal conductivity is 0.0387W / m·K. Although aerogels are synthesized using hydroxyapatite nanowires as raw materials, their microscopic morphology needs to be improved, and their hydrophobicity and heat insulation properties still need to be improved.
[0004] Hydroxyapatite sub-nanowires (HAP SNWs) have unique one-dimensional morphology, diameter or thickness comparable to the radial size of macromolecules, length greater than 1 micron, and ultra-high aspect ratio, which make them have good flexibility and can be assembled to form self-supporting materials. Assuming that hydroxyapatite sub-nanowires are assembled into three-dimensional macroscopic aerogels, it not only fills the gap between nanowires and macroscopic bulk materials, but also combines the advantages of the unique structural characteristics of aerogels and the unique physical and chemical properties of nanowires, and has a wide range of practical application value. At present, there is no technical solution for preparing aerogels with stable structure, high temperature resistance, high hydrophobicity and low thermal conductivity using hydroxyapatite sub-nanomaterials as building blocks. Summary of the invention
[0005] The purpose of the present invention is to provide a hydroxyapatite sub-nanowire aerogel and a preparation method and application thereof, so as to solve the problems existing in the above-mentioned prior art.
[0006] To achieve the above object, the present invention provides the following solutions:
[0007] The present invention provides a method for preparing hydroxyapatite sub-nanowire aerogel, comprising the following steps:
[0008] Mixing a surfactant and ethanol to obtain a mixed solvent, adding a calcium source aqueous solution, a strong alkali aqueous solution and a phosphorus source aqueous solution to obtain a mixed solution;
[0009] The mixed solution is reacted under closed conditions to obtain hydroxyapatite sub-nanowires;
[0010] dispersing the hydroxyapatite sub-nanowires to obtain a hydroxyapatite sub-nanowire solution;
[0011] The hydroxyapatite sub-nanowire solution is freeze-dried to obtain a hydroxyapatite sub-nanowire aerogel.
[0012] Preferably, the surfactant is one or more of oleylamine, oleic acid, oleyl alcohol, n-octylamine and octadecylamine, and more preferably, the surfactant is oleic acid and octadecylamine;
[0013] The surfactants of the present invention, such as oleic acid and octadecylamine, contain long-chain alkanes, and a large amount of long-chain alkanes remain in the hydroxyapatite sub-nanowires, so the prepared hydroxyapatite sub-nanowire aerogel is hydrophobic.
[0014] Preferably, the strong alkali in the strong alkali aqueous solution is one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide. More preferably, the strong alkali in the strong alkali aqueous solution is sodium hydroxide.
[0015] Preferably, the calcium source in the calcium source aqueous solution is one or more of calcium chloride, calcium nitrate, calcium acetate, calcium bromide and calcium iodide. More preferably, the calcium source in the calcium source aqueous solution is calcium chloride.
[0016] In the present invention, when the calcium source is preferably two or more of the above calcium sources, the ratio between the different types of calcium sources is any ratio;
[0017] The phosphorus source in the phosphorus source aqueous solution is one or more of sodium phosphate and its hydrate, disodium hydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, potassium phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate. More preferably, the phosphorus source in the phosphorus source aqueous solution is sodium phosphate dodecahydrate;
[0018] In the present invention, when the phosphorus source is preferably two or more of the above phosphorus sources, the ratio between different types of phosphorus sources is any ratio.
[0019] Preferably, in the mixed solution, the molar ratio of the calcium source to the phosphorus source is 5:0.5-10, more preferably 5:1-5, the molar ratio of the calcium source to the strong base is 1:5-10, more preferably 1:7, and the volume ratio of the ethanol to the total volume of the mixed solution is 1:2-6, more preferably 1:4-5.
[0020] In the present invention, when the surfactant is preferably one or more of oleylamine, oleic acid, oleyl alcohol and n-octylamine, in the mixed solution, the molar ratio of the calcium source to the surfactant is 1:10-15, more preferably 1:10-12, and the volume ratio of the surfactant to the ethanol is preferably 1-3:1, more preferably 4:5; when the surfactant is preferably octadecylamine, the molar ratio of the calcium source to the surfactant in the mixed solution is 1:1-2, more preferably 1:1.2-1.6.
[0021] Preferably, the concentration of the calcium source aqueous solution is 0.01 to 10 mol / L, more preferably 0.1 to 1 mol / L, more preferably 0.25 mol / L, the concentration of the strong alkali aqueous solution is 1 to 10 mol / L, more preferably 1 to 5 mol / L, more preferably 1.75 mol / L, and the concentration of the phosphorus source aqueous solution is 0.01 to 10 mol / L, more preferably 0.02 to 1 mol / L, more preferably 0.05 mol / L.
[0022] In the present invention, the calcium source aqueous solution, the strong alkali aqueous solution and the phosphorus source aqueous solution are preferably added dropwise in sequence.
[0023] Preferably, the reaction temperature is 150-200°C, more preferably 180°C, and the reaction time is 15-30h, more preferably 20h; after the reaction, the step of dispersing and washing the reaction products in sequence to obtain hydroxyapatite sub-nanowires is also included. More preferably, the dispersing reagent is cyclohexane, the washing reagent is anhydrous ethanol, and the number of washing times is 4 to 8 times.
[0024] In the present invention, the diameter of the hydroxyapatite sub-nanowires obtained by the reaction is 0.5-2nm.
[0025] Preferably, the mass concentration of the hydroxyapatite sub-nanowire solution is 1 to 200 mg / mL, more preferably 10 to 100 mg / mL, and more preferably 10 mg / mL.
[0026] In the present invention, the reagent for dispersing the hydroxyapatite sub-nanowires is cyclohexane.
[0027] Preferably, the freeze-drying method is pre-freezing and then freeze-drying, the pre-freezing conditions are freezing at a temperature of -196 to 0°C for 12 to 24 hours, and more preferably freezing at a temperature of -18 to 0°C for 12 hours, and the freeze-drying conditions are freeze-drying at a temperature of -60 to -40°C for 12 to 48 hours, and more preferably freeze-drying at a temperature of -40°C for 12 to 24 hours.
[0028] The purpose of the pre-freezing of the present invention is to freeze the hydroxyapatite sub-nanowire solution into a solid, so as to facilitate freeze drying.
[0029] The present invention also provides hydroxyapatite sub-nanowire aerogel obtained by the above preparation method.
[0030] The present invention also provides application of the hydroxyapatite sub-nanowire aerogel in the field of thermal insulation and heat insulation.
[0031] The present invention discloses the following technical effects:
[0032] 1) Hydroxyapatite, the building block of the aerogel of the present invention, is a natural inorganic mineral formed by natural mineralization in a living body. As a typical calcium phosphate material, hydroxyapatite has a stable phase and is easy to synthesize.
[0033] 2) The diameter of the hydroxyapatite sub-nanowires prepared by the present invention is 0.5-2nm, which is similar in size to polymer molecular chains, has a honeycomb pore structure and holes of uniform size, and can spontaneously form a three-dimensional network structure. The hydroxyapatite sub-nanowires are assembled into a three-dimensional aerogel, combining the unique structural characteristics of the aerogel and the unique physical and chemical properties of the nanowires.
[0034] 3) The aerogel structure constructed by the ultra-small hydroxyapatite sub-nanowires of the present invention is stable and resistant to high temperatures, has a certain hydrophobicity, and the water contact angle ranges from 116.05 to 138.86°. It is a natural hydrophobic material, and the thermal conductivity under 25°C environmental conditions is as low as 27.5mW / (m·K). There is a certain regularity between the hydrophobicity and thermal conductivity of the aerogel and the concentration of the hydroxyapatite sub-nanowire solution. By controlling the concentration of the hydroxyapatite sub-nanowire solution, the hydrophobicity and thermal conductivity of the aerogel can be adjusted. Therefore, the hydroxyapatite sub-nanowire aerogel prepared by the present invention has great application prospects in the fields of thermal insulation and heat insulation.
[0035] 4) The present invention first obtains hydroxyapatite sub-nanowires by a solvothermal method, and then disperses and simply freeze-dries them to prepare aerogels. The process is simple and can be mass-produced, which is beneficial to the actual production and application of aerogel materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1-2 This is a transmission electron microscopy image of hydroxyapatite sub-nanowires prepared in Example 1;
[0038] Figure 3 This is a scanning electron microscope image of HAP-50 prepared in Example 3;
[0039] Figure 4 is the Fourier transform infrared spectrum of HAP-10 prepared in Example 1;
[0040] Figure 5 is the X-ray diffraction pattern of HAP-10 prepared in Example 1;
[0041] Figure 6 This is the thermogravimetric analysis diagram of HAP-10 prepared in Example 1;
[0042] Figure 7 Schematic diagram of water contact angles of HAP-10, HAP-30, HAP-50 and HAP-100 prepared in Examples 1-4 in air;
[0043] Figure 8 The thermal conductivities of HAP-10, HAP-30, HAP-50 and HAP-100 prepared in Examples 1-4. DETAILED DESCRIPTION
[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0045] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0049] The technical solution of the present invention is further described in detail below in conjunction with embodiments.
[0050] In the following examples of the present invention, HAP-10 is an aerogel prepared from a hydroxyapatite sub-nanowire solution with a concentration of 10 mg / mL, HAP-30 is an aerogel prepared from a hydroxyapatite sub-nanowire solution with a concentration of 30 mg / mL, HAP-50 is an aerogel prepared from a hydroxyapatite sub-nanowire solution with a concentration of 50 mg / mL, and HAP-100 is an aerogel prepared from a hydroxyapatite sub-nanowire solution with a concentration of 100 mg / mL.
[0051] Example 1
[0052] 4.0 mL of oleic acid, 0.50 g of octadecylamine and 5.0 mL of anhydrous ethanol were added to a 40 mL polytetrafluoroethylene-lined autoclave and stirred for 30 min. Under vigorous stirring, 5.0 mL of calcium chloride aqueous solution (concentration 0.25 mmol / mL), 5.0 mL of sodium hydroxide aqueous solution (concentration 1.75 mmol / mL) and 5.0 mL of sodium phosphate dodecahydrate aqueous solution (concentration 0.05 mmol / mL) were slowly poured into the autoclave, sealed, reacted at 180 ° C for 20 h, and then naturally cooled to room temperature. The product was transferred and dispersed in cyclohexane under ultrasonic action, centrifuged at 10000 rpm for 5 min, and washed repeatedly with anhydrous ethanol for 6 times to obtain hydroxyapatite sub-nanowires. 0.5 g of hydroxyapatite sub-nanowires were ultrasonically dispersed in 50 mL of cyclohexane, and bubbles were removed by ultrasonication to obtain a hydroxyapatite sub-nanowire solution. The hydroxyapatite sub-nanowire solution was pre-frozen at -18°C for 12 h, and then freeze-dried at -40°C for 12 h to obtain hydroxyapatite sub-nanowire aerogel HAP-10.
[0053] Example 2
[0054] 8.0mL oleic acid, 1.0g octadecylamine and 10.0mL anhydrous ethanol were added to a 100mL polytetrafluoroethylene-lined autoclave and stirred for 30min. Under vigorous stirring, 10.0mL calcium chloride aqueous solution (concentration 0.25mmol / mL), 10.0mL sodium hydroxide aqueous solution (concentration 1.75mmol / mL) and 10.0mL sodium phosphate dodecahydrate aqueous solution (concentration 0.05mmol / mL) were slowly poured into the autoclave, sealed, reacted at 180℃ for 20h, and cooled naturally to room temperature. The product was transferred, dispersed in cyclohexane under ultrasound, centrifuged at 10000rpm for 5min, and washed repeatedly with anhydrous ethanol for 6 times to obtain hydroxyapatite sub-nanowires. 0.3g hydroxyapatite sub-nanowires were ultrasonically dispersed in 10mL cyclohexane, and bubbles were removed by ultrasound to obtain a hydroxyapatite sub-nanowire solution. The hydroxyapatite sub-nanowire solution was pre-frozen at -18°C for 12 h, and then freeze-dried at -40°C for 12 h to obtain hydroxyapatite sub-nanowire aerogel HAP-30.
[0055] Example 3
[0056] 20.0mL oleic acid, 2.5g octadecylamine and 25.0mL anhydrous ethanol were added to a 200mL polytetrafluoroethylene-lined autoclave and stirred for 30min. Under vigorous stirring, 25.0mL calcium chloride aqueous solution (concentration 0.25mmol / mL), 25.0mL sodium hydroxide aqueous solution (concentration 1.75mmol / mL) and 25.0mL sodium phosphate dodecahydrate aqueous solution (concentration 0.05mmol / mL) were slowly poured into the autoclave, sealed, reacted at 180℃ for 20h, and naturally cooled to room temperature. The product was transferred and dispersed in cyclohexane under ultrasonic action, centrifuged at 10000rpm for 5min, and washed repeatedly with anhydrous ethanol for 6 times to obtain hydroxyapatite sub-nanowires. 0.5g hydroxyapatite sub-nanowires were ultrasonically dispersed in 10mL cyclohexane, and bubbles were removed by ultrasonication to obtain a hydroxyapatite sub-nanowire solution. The hydroxyapatite sub-nanowire solution was pre-frozen at -18°C for 12 h and then freeze-dried at -40°C for 18 h to obtain hydroxyapatite sub-nanowire aerogel HAP-50.
[0057] Example 4
[0058] 20.0mL oleic acid, 2.50g octadecylamine and 25.0mL anhydrous ethanol were added to a 200mL polytetrafluoroethylene-lined autoclave and stirred for 30min. Under vigorous stirring, 25.0mL calcium chloride aqueous solution (concentration 0.25mmol / mL), 25.0mL sodium hydroxide aqueous solution (concentration 1.75mmol / mL) and 25.0mL sodium phosphate dodecahydrate aqueous solution (concentration 0.05mmol / mL) were slowly poured into the autoclave, sealed, reacted at 180℃ for 20h, and naturally cooled to room temperature. The product was transferred, dispersed in cyclohexane under ultrasonic action, centrifuged at 10000rpm for 5min, and washed repeatedly with anhydrous ethanol for 6 times to obtain hydroxyapatite sub-nanowires. 1g hydroxyapatite sub-nanowires were ultrasonically dispersed in 10mL cyclohexane, and bubbles were removed by ultrasonication to obtain a hydroxyapatite sub-nanowire solution. The hydroxyapatite sub-nanowire solution was pre-frozen at -18°C for 12 h, and then freeze-dried at -40°C for 12 h to obtain hydroxyapatite sub-nanowire aerogel HAP-100.
[0059] Example 5
[0060] 20.0 mL of oleic acid, 2.5 g of octadecylamine and 25.0 mL of anhydrous ethanol were added to a 200 mL polytetrafluoroethylene-lined autoclave. Stir for 30 min, and under vigorous stirring, 25.0 mL of calcium chloride aqueous solution (concentration 0.25 mmol / mL), 25.0 mL of sodium hydroxide aqueous solution (concentration 1.75 mmol / mL) and 25.0 mL of sodium phosphate dodecahydrate aqueous solution (concentration 0.05 mmol / mL) were slowly poured into the autoclave, sealed, reacted at 180 ° C for 20 h, and naturally cooled to room temperature. The product was transferred, dispersed in cyclohexane under ultrasound, centrifuged at 10000 rpm for 5 min, and washed repeatedly with anhydrous ethanol for 6 times to obtain hydroxyapatite sub-nanowires. 0.5 g of hydroxyapatite sub-nanowires were ultrasonically dispersed in 50 mL of cyclohexane, and bubbles were removed by ultrasound to obtain a hydroxyapatite sub-nanowire solution. The hydroxyapatite sub-nanowire solution was pre-frozen at -196°C for 12 h and then freeze-dried at -40°C for 12 h to obtain hydroxyapatite sub-nanowire aerogel HAP-10.
[0061] Performance test: The hydroxyapatite sub-nanowires prepared in the above Example 1 were subjected to transmission electron microscopy scanning test, and the aerogel HAP-10 prepared therefrom was subjected to Fourier infrared spectroscopy test, X-ray diffraction test and thermogravimetric analysis test. The aerogel HAP-50 prepared in Example 3 was subjected to electron microscope scanning, and the aerogels HAP-10, HAP-30, HAP-50 and HAP-100 prepared in Examples 1-4 were subjected to thermal conductivity test and water contact angle test. The results are shown in the figure.
[0062] Specifically, Figure 1-2 The transmission electron microscopy image shows that the diameter of the HAP SNWs prepared in Example 1 is about 1 nm.
[0063] Figure 3 The scanning electron microscope image shows that the hydroxyapatite sub-nanowire aerogel prepared by the method of the present invention has a honeycomb pore structure with pores of uniform size.
[0064] Figure 4 The Fourier transform infrared spectrum shows that the characteristic peak of PO stretching vibration in HAP SNWs is located at 1024 cm -1 and 1072cm -1 This confirms the formation of HAP, and the absorption peaks are located at 1449 cm -1 and 1548cm -1 (C=O), 2852cm -1 and 2922cm -1 (-CH2 and -CH3), which confirms the presence of oleic acid in HAP.
[0065] Figure 5The X-ray diffraction pattern shows that the peaks in the spectrum are not sharp and can be matched with the PDF card (NO.99-000-1643) of Ca5(PO4)3(OH), which confirms that the main phase of the generated sub-nanowires is HAP with low crystallinity.
[0066] Figure 6 The thermogravimetric curves of HAP SNWs confirmed the thermal stability of HAP SNWs at high temperatures. HAP SNWs remained stable at 800°C and had a residual weight greater than 20% at 1000°C. The observed mass loss mainly came from a small amount of water (weight loss at 0-100°C) and oleic acid (weight loss at 200°C-400°C), and the pyrolysis rate reached a peak at around 350°C. Thermogravimetric analysis showed that the hydroxyapatite sub-nanowire aerogel skeleton prepared by the present invention had excellent thermal stability.
[0067] Figure 7 It is shown that the aerogels prepared in Examples 1-4 all exhibit a certain degree of hydrophobicity, with contact angles ranging from 116.05 to 138.86°, among which the water contact angle (WCA) of the HAP-10 aerogel prepared in Example 1 is 138°, which is due to the high surface roughness caused by the multi-level micro / nano structure and the large number of long alkane chains attached to the surface of the aerogel giving it hydrophobicity. As the concentration of hydroxyapatite sub-nanowires increases, the WCA of the aerogel gradually decreases.
[0068] Figure 8 The thermal conductivity of the aerogels prepared in Examples 1-4 was measured. The thermal conductivity of the aerogels increased with the increase of the initial HAP sub-nanowire concentration. The thermal conductivity of the HAP-10 aerogel prepared in Example 1 was very low, only 27.5 mW / (m·K), which was close to the thermal conductivity of air (25 mW / (m·K)). The thermal conductivity of the HAP-100 aerogel prepared in Example 4 was 39.98 mW / (m·K).
[0069] It can be seen from the results that the preparation method of the present invention can be used to obtain aerogels with good hydrophobicity and low thermal conductivity. The thermal conductivity of the HAP-10 aerogel is 27.5 mW / (m·K), which is close to the thermal conductivity of air under ambient conditions (25 mW / (m·K)). Therefore, the aerogels prepared by the present invention also have great application prospects in the fields of thermal insulation and heat insulation.
[0070] The above examples were repeated many times, and similar results were obtained, indicating that the preparation method of the present invention has good repeatability.
[0071] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing hydroxyapatite sub-nanowire aerogel, characterized in that: The following steps are involved: Mixing a surfactant and ethanol to obtain a mixed solvent, adding a calcium source aqueous solution, a strong base aqueous solution and a phosphorus source aqueous solution to obtain a mixed solution, wherein the molar ratio of the calcium source to the phosphorus source is 5:0.5-10, and the molar ratio of the calcium source to the strong base is 1:5-10; The mixed solution is reacted under closed conditions to obtain hydroxyapatite sub-nanowires; Dispersing the hydroxyapatite sub-nanowires to obtain a hydroxyapatite sub-nanowire solution, wherein the dispersing agent is cyclohexane; The hydroxyapatite sub-nanowire solution is freeze-dried to obtain a hydroxyapatite sub-nanowire aerogel.
2. The preparation method according to claim 1, characterized in that: The surfactant is one or more of oleylamine, oleic acid, oleyl alcohol, n-octylamine and octadecylamine; The strong alkali in the strong alkali aqueous solution is one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide.
3. The preparation method according to claim 1, characterized in that: The calcium source in the calcium source aqueous solution is one or more of calcium chloride, calcium nitrate, calcium acetate, calcium bromide and calcium iodide; The phosphorus source in the phosphorus source aqueous solution is one or more of sodium phosphate and its hydrate, disodium hydrogen phosphate, sodium dihydrogen phosphate, phosphoric acid, potassium phosphate, dipotassium hydrogen phosphate, potassium dihydrogen phosphate, ammonium phosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate.
4. The preparation method according to claim 1, characterized in that: The volume ratio of the ethanol to the total volume of the mixed solution is 1:2-6.
5. The preparation method according to claim 1, characterized in that: The concentration of the calcium source aqueous solution is 0.01-10 mol / L, the concentration of the strong alkali aqueous solution is 1-10 mol / L, and the concentration of the phosphorus source aqueous solution is 0.01-10 mol / L.
6. The preparation method according to claim 1, characterized in that: The reaction temperature is 150-200° C., the reaction time is 15-30 hours, and after the reaction, the step of dispersing and washing the reaction products in sequence to obtain hydroxyapatite sub-nanowires is also included.
7. The preparation method according to claim 1, characterized in that: The mass concentration of the hydroxyapatite sub-nanowire solution is 1-200 mg / mL.
8. The preparation method according to claim 1, characterized in that: The freeze-drying method comprises pre-freezing and then freeze-drying, wherein the pre-freezing condition is freezing at a temperature of -196 to 0°C for 12 to 24 hours, and the freeze-drying condition is freeze-drying at a temperature of -60 to -40°C for 12 to 48 hours.
9. The hydroxyapatite sub-nanowire aerogel obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the hydroxyapatite sub-nanowire aerogel according to claim 9 in the field of thermal insulation and heat insulation.
Citation Information
Patent Citations
Hydroxyapatite superlong nanowire aerogel
CN107892286A
Aramid nanofiber-based composite aerogel as well as preparation method and application thereof
CN115572407A
Preparation method of flexible ultrafine sub-nanometer wire with hydroxyapatite characteristics
CN105217593A
Hemostatic aerogel with ultra-long hydroxyapatite nanowire, and preparation method and application of hemostatic aerogel
CN113679877A